Prognostic value of ventricular function assessed by speckle tracking echocardiography in patients with sepsis - Ricarte Bratti, Juan Pablo (2017)
Background. The prognostic value of left ventricular dysfunction in patients with sepsis is unknown. Speckle tracking echocardiography (STE) is a novel, sensitive method for assessing ventricular function, capable of unmasking myocardial dysfunction not detected with conventional echocardiography. We assessed STE in patients with sepsis to determine whether it is associated with mortality. Material and methods. Between April 2015 and March 2016, patients aged ≥18 years admitted to the intensive care unit with the diagnosis of sepsis and without previous cardiomyopathy were prospectively imaged using transthoracic echocardiography. Left ventricular function was assessed using conventional methods and STE. Mortality was assessed over 30 days. Results. Eighteen patients were included and the 30-day mortality rate was 27.7%. The ejection fraction (EF) estimated using the Simpson method was similar between patients who died and those who survived; however, the ventricular function determined using STE in the 4-chamber view was significantly lower in patients who died (-14% ± 5 vs -17% ± 2, p=0.028). No significant differences were observed in the 2-chamber view (alive: -16 ± 3, dead: -14 ± 5, p=0.182), long apical axes view (alive: -17 ± 2, dead: -15 ± 4, p=0.434) or global strain (alive: -17 ± 2, dead: -14 ± 4, p=0.118). Conclusion. In patients with sepsis, ventricular function assessed with STE in the 4-chamber view was more sensitive than EF in detecting dysfunction and better predicted 30-day mortality. Larger trials will be necessary to corroborate these findings. Insuf Card 2017; 12(1): 2-8.